Phytochemical Screening, Antimicrobial and Antioxidant Properties of the Leaf Fractions of Scoparia Dulcis - Danjuma, Kabir; Kabir Abdu; Imrana Lawan; Moses Jibrin; Magaji Amayindi (Indonesian Journal of Health Research and Development, 2025)
Background: Scoparia dulcis is a medicinal plant found in low and high temperature areas. Aims and scope: This study was done to examine the effect of solvent’s polarity on extraction yield, evaluate phytochemicals, antioxidant and antimicrobial capacity of Scoparia dulcis.Methods: Solvents of different polarities were used to fractionate the ethanol crude by maceration. Phytochemicals screening was done using standard methods, and DPPH experiment was used to screen for antioxidant capacity. Agar diffusion method was used to evaluate the leaf extracts for antimicrobial potential.Results: Methanol gives highest yield (10.73%), followed by cetone (9.56%), chloroform (6.94%), and petroleum ether (5.16%). Glycosides and anthroquinones were not found, but alkaloids, terpenoids, tannins, saponins, steroids, polyphenols, flavonoids, and reducing sugar were qualitatively detected. Scopariadulcis also showed significant antimicrobial capacity; with acetone displaying highest capacity, followed by methanol and chloroform extracts. The results also showed remarkable antimicrobial capacity with acetone exhibiting largest inhibition zone. The extracts also produced Antioxidant capacity with chloroform having highest activity (IC50 = 29.6288 µg/mL), followed by petroleum ether (IC50 = 34.5308 µg/mL), methanol (), and acetone (IC50 = 100.3340 (µg/mL). ANOVA test shows the plant extract has significant antimicrobial and antioxidant capacity at P>0.05.Conclusion: Scoparia dulcis leaf extracts contain phytochemicals that possess antimicrobial and antioxidant potentials. This research is the first of its kind carried out on this plant in northern Nigeria. The plant is a valuable medicinal plant that can be used for therapeutic applications.